Peran Strategis Kompetensi, Kompensasi, dan Motivasi dalam Peningkatan Kinerja Pegawai - Hanggono, Bayu (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
In modern organizations, improving employee performance is the main focus for achieving the company's strategic goals. Competence, compensation and motivation are important factors that influence employee productivity and work effectiveness. A deep understanding of the strategic role of these three factors can help companies design effective policies to improve employee performance. This research aims to analyze the strategic role of competency, compensation and motivation in improving employee performance. This study seeks to identify the extent to which these three factors contribute to employee performance and provide practical recommendations for improving human resource management. This research uses a quantitative approach with survey methods. Data was collected through questionnaires distributed to employees. Data analysis was carried out using multiple regression to determine the influence of each independent variable (competence, compensation and motivation) on the dependent variable (employee performance). The results of the analysis show that competence, compensation and motivation have a positive and significant influence on employee performance. Competence shows the greatest influence, followed by motivation and compensation. These findings underscore the importance of investing in training and development, as well as providing competitive compensation and effective motivation policies.